2021
DOI: 10.4103/apjon.apjon_50_20
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Blood Transfusion – What Nurses Know and Perform: A Cross-Sectional Study from A Tertiary-Level Cancer Hospital in Rural Kerala

Abstract: Objective: Nursing professionals are expected to have updated knowledge of clinical blood transfusion guidelines while catering to cancer patients requiring bedside transfusions. Methods: A cross-sectional study was conducted to evaluate the knowledge and current practice of nurses at a tertiary-level cancer hospital in rural Kerala using a pretested self-administered structured 20-item questionnaire, and results were analyzed. Results: Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
3
4
1
Order By: Relevance
“…The study emphasized on the knowledge of ABO and RhD compatibility, and it was observed that more than half of the participants who answered incorrectly lacked this knowledge. However, our results were not as favorable as those reported by Jogi et al (2021), who found a higher percentage of nurses (62.01%) were aware of universal recipient blood groups for ABO and RhD compatibility.…”
Section: Inadequate Knowledge Of Blood Transfusioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study emphasized on the knowledge of ABO and RhD compatibility, and it was observed that more than half of the participants who answered incorrectly lacked this knowledge. However, our results were not as favorable as those reported by Jogi et al (2021), who found a higher percentage of nurses (62.01%) were aware of universal recipient blood groups for ABO and RhD compatibility.…”
Section: Inadequate Knowledge Of Blood Transfusioncontrasting
confidence: 99%
“…These results contradict with previous studies by Haza Azdiana et al (2016), which highlighted the influence of training courses, policy availability, and age on knowledge levels. Consistent with Jogi et al (2021), the study reveals that longer work experience is linked to better knowledge. Surprisingly, the level of education does not significantly impact knowledge, contradicting Aneke et al (2017).…”
Section: Association Between Social Demographic With Knowledge Blood ...supporting
confidence: 77%
“…More than half of the nurses in this study had a moderate level of knowledge about blood transfusion. Earlier studies also showed that nurses' knowledge of this procedure was low or moderate [12,13,17,18,20,[22][23][24][25][26]. Since transfusion of blood and blood products is a multistage procedure, our studies and those mentioned above aim to be used to identify risky parts of the transfusion process and at-risk populations of blood recipients to ensure safe blood administration in intensive care units.…”
Section: Discussionmentioning
confidence: 88%
“…The researchers designed the questionnaire on nurses' knowledge of the blood transfusion procedure based on the World Health Organization (WHO) Clinical Transfusion Procedure [15], National Guidelines for Clinical Use of Blood [16], and earlier study [17][18][19][20]. Before use, the questionnaire was reviewed by a panel of experts consisting of three nurses with academic education, more than ten years of work experience in the ICU, two doctors, one specialist in anaesthesia and intensive care, and one specialist in transfusionology.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation